Anne of green gables - Montefiore, Mary Sebag (LOndon: Usborne, 2014)
his is the classic story by L.M. Montgomery retold for children ready to tackle longer and more complex stories. The Cuthberts of Green Gables asked for a boy from the orphanage to help them out around the farm, so they are rather surprised when a talkative, red-headed little girl steps off the train to meet them
Keywords: Children's stories